42.8k views
2 votes
100 + (n - 2) ^ = 149 how do I solve this what is the first step??

User Podiluska
by
7.1k points

1 Answer

5 votes

The given expression is


100+(n-2)^2=149

First, we have to subtract 100 on each side


\begin{gathered} 100-100+(n-2)^2=149-100 \\ (n-2)^2=49 \end{gathered}

Hence, the answer is the first option, that's the first step.

The reason for this first step is because we can't take a square root without getting rid of the terms 100, otherwise, the process would be wrong.

User Alessandro Peca
by
7.4k points